Comparison between Off-Pump and On-Pump Beating Heart Coronary Artery Bypass Grafting - Matsuhashi, Kazuki; Takami, Yoshiyuki; Maekawa, Atsuo; Yamana, Koji; Akita, Kiyotoshi; Amano, Kentaro; Takagi, Yasushi (The Thoracic and Cardiovascular Surgeon, 2024)
Background Although coronary artery bypass grafting (CABG) is performed via three different techniques, conventional, on-pump beating heart CABG (ONBHCAB), or off-pump CABG (OPCAB), data are limited to compare ONBHCAB with OPCAB.Methods We retrospectively investigated the postoperative cardiac biomarkers, creatine kinase-MB (CK-MB), and troponin I (cTnI), and early and late outcomes in 806 patients undergoing isolated ONBHCAB or OPCAB between February 2008 and September 2022. To eliminate the bias between different groups, propensity score matching was conducted to validate the findings.Results After matching, the number of each study group totaled 270 patients. In both complete and matched cohorts, early outcomes, including morbidities and mortalities, were similar. However, cTnI and CK-MB levels were significantly higher after ONBHCAB than after OPCAB with median peak cTnI of 9.85 versus 4.60 ng/mL and median peak CK-MB of 48.45 versus 17.10 ng/mL in the matched cohort, which were quite low, below the threshold for values defining perioperative myocardial infarction. At follow-up of 73 ± 45 months, the overall actuarial survival rates were similar between the ONBHCAB and OPCAB patients (86 vs. 87% at 5 years and 64 vs. 68% at 10 years, respectively, in the matched cohort).Conclusion ONBHCAB may be a comparable alternative to OPCAB with similar early and late outcomes, despite higher elevation of postoperative cardiac biomarkers. ONBHCAB provides more efficient hemodynamic support, providing a better surgical visual field, than OPCAB while reducing the risk of incomplete revascularization.
Keywords: coronary artery bypass grafting; on-pump beating heart; off-pump; cardiac biomarkers; cardiac troponin I